Characterization of a soft tissue-mimicking agar/wood powder material for MRgFUS applications - Drakos, Theocharis; Giannakou, Marinos; Menikou, Georgios; Constantinides, Georgios; Damianou, Christakis A. (My University, 2021)
This study describes the development and characterization of an agar-based soft tissue-mimicking material (TMM) doped with wood powder destined for fabricating MRgFUS applications. The main objective of the following work was to investigate the suitability of wood powder as an inexpensive alternative in replacing other added materials that have been suggested in previous studies for controlling the ultrasonic properties of TMMs. The characterization procedure involved a series of experiments designed to estimate the acoustic (attenuation coefficient, absorption coefficient, propagation speed, and impedance), thermal (conductivity, diffusivity, specific heat capacity), and MR properties (T1 and T2 relaxation times) of the wood-powder doped material. The developed TMM (2% w/v agar and 4% w/v wood powder) as expected demonstrated compatibility with MRI scanner following images artifacts evaluation. The acoustic attenuation coefficient of the proposed material was measured over the frequency range of 1.1–3 MHz and found to be nearly proportional to frequency. The measured attenuation coefficient was 0.48 dB/cm at 1 MHz which was well within the range of soft tissue. Temperatures over 37 °C proved to increase marginally the attenuation coefficient. Following the transient thermoelectric method, the acoustic absorption coefficient was estimated at 0.34 dB/cm-MHz. The estimated propagation speed (1487 m/s) was within the range of soft tissue at room temperature, while it significantly increased with higher temperature. The material possessed an acoustic impedance of 1.58 MRayl which was found to be comparable to the corresponding value of muscle tissue. The thermal conductivity of the material was estimated at 0.51 W/m K. The measured relaxation times T1 (844 ms) and T2 (66 ms) were within the range of values found in the literature for soft tissue. The phantom was tested for its suitability for evaluating MRgFUS thermal protocols. High acoustic energy was applied, and temperature change was recorded using thermocouples and MR thermometry. MR thermal maps were acquired using single-shot Echo Planar Imaging (EPI) gradient echo sequence. The TMM matched adequately the acoustic and thermal properties of human tissues and through a series of experiments, it was proven that wood concentration enhances acoustic absorption. Experiments using MR thermometry demonstrated the usefulness of this phantom to evaluate ultrasonic thermal protocols by monitoring peak temperatures in real-time. Thermal lesions formed above a thermal dose were observed in high-resolution MR images and visually in dissections of the proposed TMM.
Keywords: Tissue-mimicking materials; Agar; Ultrasound; MRgFUS